The pre-history of the significance of ousia: An analysis of the heideggerian interpretation of ousia as presentness (Anwesenheit) (Revista Archai, 2018)
How did the Greeks understand the significance of Î¿á½ÏƒÎ¯Î± before it became an expression dominated by the platonic and aristotelic thought? Is Heidegger correct to interpret this pre-philosophical comprehension as constant presentness (ständige Anwesenheit) or is such interpretation a characteristic distortion from the German thinker? Through the establishment of etymological and philological criteria and of the philosophical use of the word Î¿á½ÏƒÎ¯Î±, it is aimed not only to clarify its daily use, that means, pre-philosophical, but also to prove the heideggerian interpretation. From the undertaken examination it resulted that the pre-philosophical comprehension of Î¿á½ÏƒÎ¯Î± carries the meanings of “ownership”, “goods”, “residence”, “fortune”. However, the undertaken examination also demonstrated that it is only possible as such and in coherence to the philosophical use of the term if such a daily comprehension is already orientated from a pre-comprehension of Î¿á½ÏƒÎ¯Î± as constant presentness. The reached conclusion is that the heideggerian interpretation under no circumstances constitutes a misrepresentation or distortion of the analysed term, but an authentic immersion in the Greek language and, above all, a legitimate appropriation of the Greek thought and vocabulary.